2012
DOI: 10.1021/ja306265n
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticle-Enabled Real-Time Ligation Chain Reaction for Ultrasensitive Detection of DNA

Abstract: A simple and ultrasensitive colorimetric DNA assay based on the detection of the product of a ligation chain reaction (LCR) and the use of gold nanoparticles (AuNPs) as signal generators has been developed. During LCR, the AuNPs were ligated together, resulting in a distinct color change in real time after a sufficient number of thermal cycles. The cumulative nature of the protocol produced a detection limit of 20 aM with a selectivity factor of 10(3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(78 citation statements)
references
References 21 publications
1
75
0
2
Order By: Relevance
“…Recently, it was shown that Au NPs could be combined with DNA amplification through the ligation chain reaction (LCR) (Shen et al, 2012). In the LCR, DNA is amplified exponentially, much in the same way as in the PCR reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was shown that Au NPs could be combined with DNA amplification through the ligation chain reaction (LCR) (Shen et al, 2012). In the LCR, DNA is amplified exponentially, much in the same way as in the PCR reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction results in an exponential amplification, as each ligated target will also function as a template for ligation of reverse probes complementary to the original ligation probes. Using this, Shen et al (2012) linked together DNA probes immobilized on Au NPs only in the presence of the target sequence. As a result, an increasing amount of Au NPs irreversibly aggregated with increasing number of ligation cycles, causing a gradual shift in the absorbance of the Au NP solution due to LSPR adsorption band coupling.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a period of 12 h hybridization/DSN incubation produced a detection limit as low as 50 aM, corresponding to 30 target RNA strands/μL. On the other hand, as a practically homogeneous assay, much improved reproducibility was expected (Yang et al, 2014;Deng et al, 2013Deng et al, , 2014Gao et al, 2013;Shen et al, 2013Shen et al, , 2012. For instance, the standard derivations of 10 duplicated tests at 2.0 and 200 fM were found to be 9% and 7%, respectively.…”
Section: Calibration Studymentioning
confidence: 99%
“…Many detection systems have been developed by making use of enzymes as amplifiers because of the low abundance of targets in natural environments. Amplificatory tools, such as polymerase (Manrao et al, 2012), ligase (Shen et al, 2012;Wee et al, 2012) and exonuclease (Ju et al, 2012;Xuan et al, 2012), in DNA detection offer exquisite sensitivity and are commonly used to follow target-probe hybridization. However, these enzyme-based assays are labor-intensive, require complex operation, and have a relatively high cost.…”
Section: Introductionmentioning
confidence: 99%